1999
DOI: 10.1016/s0021-9673(98)00970-4
|View full text |Cite
|
Sign up to set email alerts
|

Conductimetric detection of anions of very weak acids by incomplete suppressed ion chromatography

Abstract: A novel method, incomplete suppressed conductimetric detection, has been developed for the determination of anions of very weak acids. The principle of the method was discussed. Theoretical considerations involved the choice of background conductance and its effect on linearity and detection limits. Results showed that for both arsenous acid and boric acid, the sensitivity was improved greatly with low background conductance, compared with the suppressed conductimetric method. With 250 mg / l boric acid, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Incomplete suppressed IC is discussed by Huang et al (46). He suggested to operate the suppressor in a mode such that the eluent is just barely neutralized, so that the arsenite will remain in an ionic state.…”
Section: Analytical Techniques For Arsenic Speciationmentioning
confidence: 99%
“…Incomplete suppressed IC is discussed by Huang et al (46). He suggested to operate the suppressor in a mode such that the eluent is just barely neutralized, so that the arsenite will remain in an ionic state.…”
Section: Analytical Techniques For Arsenic Speciationmentioning
confidence: 99%
“…Caliamanis et al have developed an altogether different approach. A commercial suppressor unit bearing cation exchange membranes and an NaOH−EDTA external bathing solution is used to convert HX to NaX. Yuan et al suggested operating a suppressor in a mode such that the eluent is just short of completely neutralized. However, it is very difficult to maintain such operation with a constant background, low-noise environment.…”
mentioning
confidence: 99%